Quizizz as Fun Multiplying Learning Media in English Lecturing Process - Angga Prasongko (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2021)
Indonesia has a great opportunity to use technological developments in the current 4th industrial revolution. The opportunity is based on the fact that from the total population of Indonesia, more than half of them are active internet users. The largest group of internet users in Indonesia is at the age of students, these groups of students are in the middle to college student level. To occupy the need for technology-based learning, it is necessary to modify and have some innovations to various learning tools in learning activities. This qualitative descriptive research will discuss the use of technology-based learning media with Quizizz as an application in English learning lecturing process. This study involved students of the 1st level of accounting study program who had passed English Class at the Universitas Islam Kadiri-Kediri (UNISKA). In general, the results of the study indicate that English lecturing process using the Quizizz is a fun and effective activity so that it is expected to continue to be used in further lecturing activities.